Somewhere over the rainbow: Sexual orientation discrimination in Germany - Stephan Humpert (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
This paper observes sexual orientation based differences in German incomes. Gay men and lesbian women sort themselves into different occupations and sectors than their heterosexual counterparts. I find evidence that cohabitating gay men have an income penalty of 9 to 10 percent compared with married men, while lesbian women have a premium of about 10 to 12 percent compared with married women. Lesbians in a registered same-sex union have an income gain of about 16 to 21 percent, while the effect for men is not statistically significant. There is evidence that gay households have 9 to 15 percent higher household income than mixed-sex couples. The results for lesbian household income are not statistically significant.
Keywords: J31; J16; J22; 330; Wage Discrimination; Labor Supply; Sexual Orientation; Homosexualität; Lohndifferenzierung; Arbeitsangebot; Schätzung; Deutschland